STRATEGI PENGEMBANGAN FASHION ISLAMI DALAM DINAMIKA PERSAINGAN BISNIS DI INDONESIA - Hanni Haernai; Azis Nurkholis Majid; Dede Ananta K Perangin- Angin (Jurnal Sosio dan Humaniora (SOMA), 2026)
The Islamic fashion industry in Indonesia has experienced rapid growth in line with increasing public awareness of halal lifestyles and Islamic identity. However, the rising number of business players has also led to increasingly intense competition, both from local and global brands. This article aims to analyze effective development strategies for Islamic fashion in addressing the dynamics of business competition in Indonesia. The method used is a literature review and descriptive analysis of industry trends, Muslim consumer behavior, and marketing strategies implemented by national Islamic fashion brands. The findings indicate that strategies emphasizing religious value differentiation, design innovation, consistent branding, and optimized digital marketing serve as key factors in maintaining competitiveness. This study recommends that Islamic fashion industry players strengthen the integration between spiritual values and modern business strategies to create sustainable competitive advantage